Mnemonics- An Effective Tool for Vocabulary Building - Arora, Shweta; Joshi, Kavita A.; Pant, Garima; Bisht, Narendra; Sharma, Kanika (International Journal of Psychosocial Rehabilitation, 2020)
Enhanced vocabulary is an indispensable part of effective communication. However, very few people possess strong word power. Good vocabulary is not an innate property of an individual. Deliberate efforts to improve wordpower can result into improved expression of ideas through rich and wise usage of words. The steriotypical method of learning and retaining new words (rote learning) has not given desired output. In the present study, the researchers have contemplated the issue and used mnemonics as an effective vocabulary building tool. The results of the study reflect the effectiveness of mnemonics as a vocabulary booster.